A STUDY ON CUSTOMERS PERCEPTION ABOUT MARKETING 4.0 STRATEGIES (International Journal of Food and Nutritional Sciences, 2022)
The impact of Marketing 4.0 strategies and practices on customer satisfaction and engagement is examined in this study report. The study uses a quantitative methodology, gathering information from 310 people who represent a broad sample using a standardized questionnaire. The study aimed to investigate the impact of Marketing 4.0 on customer involvement and evaluate its implications on customer satisfaction. The results show that customer engagement levels are greatly increased by implementing Marketing 4.0 methods, such as co-creation, personalized experiences, and interactive engagements. Customer satisfaction also rises with the implementation of Marketing 4.0 strategies, which include customized offerings, easy-to-use interfaces, and effective avenues for contact.